Understanding Extensive Reading Implementation Issues: Insights From Indonesian Tertiary EFL Students’ Experiences - Afiani Fitriasti; Endang Setyaningsih; Hefy Sulistyawati (STAI Hubbulwathan Duri, 2024)
This case study investigates issues regarding the implementation of extensive reading (ER) and explores students’ experiences and feelings during an ER course in higher education. The participants were five female university EFL students who were selected purposively. Data were collected through questionnaires, interviews, and respondents’ diaries and processed using the stages of an interactive model. The analysis yields two major findings. First, the students held contrasting views on ER with two respondents reporting pleasure while the other expressed motivation, joylessness, and challenge. This finding can be attributed to the lack of freedom in choosing what to read and the unfit level of reading. Second, five factors are attributed to the success of ER: love for reading/ self-motivation, freedom to choose what to read, supportive reading environment, lecturers’ guidance, and variety of ER-based activities. These findings imply that the core principles of ER should be instituted. Failure to maintain these principles may deter students’ sustained engagement in ER.